1964
DOI: 10.1063/1.1725428
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diffraction and Nuclear Quadrupole Resonance Studies of Chromium Trichloride

Abstract: The infinite-layer compound CrCl3 is found to undergo a first-order phase transformation near 240°K. The crystal structures of the high- and low-temperature phases have been elucidated by detailed x-ray diffraction and 35Cl nuclear quadrupole resonance studies. The previously reported structure for CrCl3 is shown to be incorrect. The present single-crystal diffraction results at 298° and 225°K give monoclinic (C2/m: a0=5.959 Å, b0=10.321, c0=6.114 Å, β=108.49°) and rhombohedral (R3̄: a0=5.942 Å, c0=17.333 Å) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
131
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(150 citation statements)
references
References 21 publications
17
131
2
Order By: Relevance
“…Using single crystal diffraction, Morosin and Narath [37] demonstrated that CrCl 3 adopts the monoclinic space group C2/m at room temperature and the rhombohedral space group R3 at 225 K. They used nuclear quadrupole resonance to identify the phase transformation temperature as 240 K. The crystallographic phase transitions involves mainly a change in the layer-to-layer shift in the stacking sequence. The intralayer structure remains nearly the same, with an ideal honeycomb net of Cr in the rhombohedral structure and a slightly distorted honeycomb net in the monoclinic structure [18,37]. For example, in CrCl 3 the in-plane Cr-Cr distances are 3.431Å at 225 K (rhombohedral) and 3.440 and 3.441Å at 298 K (monoclinic) [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using single crystal diffraction, Morosin and Narath [37] demonstrated that CrCl 3 adopts the monoclinic space group C2/m at room temperature and the rhombohedral space group R3 at 225 K. They used nuclear quadrupole resonance to identify the phase transformation temperature as 240 K. The crystallographic phase transitions involves mainly a change in the layer-to-layer shift in the stacking sequence. The intralayer structure remains nearly the same, with an ideal honeycomb net of Cr in the rhombohedral structure and a slightly distorted honeycomb net in the monoclinic structure [18,37]. For example, in CrCl 3 the in-plane Cr-Cr distances are 3.431Å at 225 K (rhombohedral) and 3.440 and 3.441Å at 298 K (monoclinic) [37].…”
Section: Resultsmentioning
confidence: 99%
“…Weak magnetic anisotropy and weakly antiferromagnetic interlayer interactions are also reported from spin wave analysis [36]. In addition, CrCl 3 is known to undergo a crystallographic phase transition near 240 K, similar to CrBr 3 and CrI 3 , corresponding to a change in the layer stacking arrangement and a transition from monoclinic (C2/m) at high temperature to rhombohedral (R3) at low temperature with little change in the intralayer structure [18,37].…”
Section: Introductionmentioning
confidence: 97%
“…All three of the layered chromium trihalides are known to undergo temperature induced crystallographic phase transitions between the AlCl 3 and BiI 3 structure types [16,73]. At high temperatures all three adopt the AlCl 3 structure and transition to the BiI 3 structure upon cooling.…”
Section: Compoundmentioning
confidence: 99%
“…In order to elucidate the anomalous structural and magnetic behaviors of α-RuCl 3 , we first focus on the sister compound CrCl 3 , which undergoes a structural phase transition from the monoclinic structure (C2/m) to the rhombohedral structure (R3) at T S = 240 K 32,33 . Unlike α-RuCl 3 , CrCl 3 forms a conventional Heisenbergtype magnet having magnetic ordering at T N = 17 K and thus its low-energy excitation is given by conventional spin wave without spin fractionalization 32 .…”
Section: A Phonon Raman Spectra Of Crcl3mentioning
confidence: 99%
“…Presently experiments on single layer materials are still rather rare 17 . As such, the comparison between α-RuCl 3 and its sister compound CrCl 3 will shed light on investigating the relation between the structure and Kitaev magnetism because CrCl 3 having Heisenberg interactions undergoes the monoclinic-to-rhombohedral structure transformation at 240 K 32,33 . In Kitaev materials, Raman spectroscopy presents a powerful experimental tool as it probes Majorana fermion density of states 5 .…”
Section: Introductionmentioning
confidence: 99%